Overcoming the neutral zone trap : hockey's agents of change - MacDonald, Cheryl A.; Edwards, Jonathon R. J. (University of Alberta Press, 2021)
"This engaging interdisciplinary collection seeks to shed light on narratives and research that challenge hockey's norms, push its boundaries, and provide new ways of conceptualizing its role in North American culture. The volume's editors use the metaphor of the neutral zone trap to explore how traditional ideologies and practices within the sport have contributed to exclusion and the misperception of various ways of existing in its community. The book includes both personal and scholarly accounts of agents of change--people, ideas, and events--that confront the challenges associated with making hockey a more progressive space. By peeling back assumptions and common understandings of hockey culture, Overcoming the Neutral Zone Trap opens up critical discussions of previously underexplored topics as they relate to the women's game, Indigenous participation, viable career pathways, masculine identities, hockey parents, mental health, and social media. Fans and experts alike will find much in these pages to deepen their understanding of hockey's social implications. Contributors: Angie Abdou, Kieran Block, Cam Braes, William Bridel, Judy Davidson, Jonathon R.J. Edwards, Catherine Houston, Colin D. Howell, Chelsey H. Leahy, Roger G. LeBlanc, Cheryl A. MacDonald, Fred Mason, Brock McGillis, Vicky Paraschak, Brett Pardy, Ann Pegoraro, Kyle A. Rich, Tavis Smith, Noah Underwood"--